Identifikasi Jenis Epifit Dan Tumbuhan Yang Menjadi Penopangnya Di Blok Perlindungan Dalam Kawasan Taman Hutan Raya Wan Abdul Rachman - Gesta Rama Noprian Nawawi; Indriyanto Indriyanto; Duryat Duryat (Department of Forestry, Faculty of Agriculture, University of Lampung, 2014)
Epiphytic is one among the plants that attaches and grows on other plants for sunlight, water, air, and minerals. The existence of epiphytes is very important for forest ecosystems due its ability to provide a place for the ants and the other organisme. The objective of this study were to identify the species of epiphytes, species of cantilever plant, and to know the number of cantilever plant species associated with the species of epiphytes in Wan Abdul Rahman Great Forest Park. This research was conducted at the protection block, Wan Abdul Rahman Great Forest Park, particularly in the area of Way Balau Sub-watershed. This research was conducted during September to October 2013. Epiphytes and cantilever plants species were inventoried in a sampling intensity of 0,2% taken from 796,50 ha of total area of protection blocks, therefore the large of sample plot is 1,593 ha. The size of each sample plot is 400 m2 or 20 m x 20 m, therefore the total number of sample plots are 40 plots. Observed variables were the species and the number of epiphytes , species of cantilever plant and its number, and the importance alue index for each species. The result of the study showed that plant are 7 species of epiphytes and 16 species of cantilever plant. The highest importance value index (IVI) of epiphytes is paku sepat (59,14%). Â The highest IVI of cantilever plant is pulai (30,91%). The most abundant cantilever plant growed by epiphytes is pulai (Alstonia scholaris), pinangsi (Villebrunea rubescens), enau (Arenga pinnata), and medang gabong (Litsea firma). Result of the study showed that epiphytic mostly found on the cantilever plant that has thicker bark, groove bark, stringy bark, and a tough bark. Keywords: block protection forest park wan abdul rahman, epiphytes , epiphytic plants crutch